Desastres naturais: uma análise dos decretos de estiagem e seca no Estado do Rio Grande do Norte - Ribeiro, Marcos Samuel Matias (2016)
The Natural Disasters (DN) are established by the occurrence of natural phenomena in areas or regions inhabited, and characterized by the fact that its impact damage to the affected population. If undamaged to the company or happen in areas not occupied, the phenomenon is considered just a natural event. The Natural Disaster occurrences originate great problems and damage to the affected societies besides causing great human losses. The objective is to analyze the occurrence of DN in nineteen micro-regions of Rio Grande do Norte state, in the period 1991-2012, drawing a parallel with the records over time of rainfall thresholds. We used statistical techniques, as a spatial analysis to build thematic maps to identify areas with increased risk, and the chi-square test to verify associations between variables. The Standardized Precipitation Index (SPI) was considered, aiming to highlight the weather conditions of the areas analyzed at the time of publication of Decree of the State of Emergency and Public Calamity. The results showed a significant increase of 98,7% in the records of events for the state, once in eleven (11) years were first registered 535 occurrences and the subsequent 11 years were recorded 1.063, a total of 2.447,683 people affected by DN. For the state, the phenomena that most frequently presented were: the drought / dry (81,1%), flash floods and floods (18,9%), from the relations of factors with characteristics between the natural and social. The data show statistically significant relationships between the occurrences for the two periods, and its relationship with the annual cumulative average rainfall. Understanding this behavior over time will lead the competent authorities, to identify the conditions that is society, enabling the direct actions and effective public policies in the management to mitigate the risk of natural disasters.